Reorienting information searching research by applying a situated abilities perspective - Gerd Berget (Information Research: An International Electronic Journal)
Introduction. In studies of information searching, people are often characterised with perpetual physical, sensory and cognitive abilities. Situational factors that may affect human abilities are less considered, although they may have an impact on information searching behaviour. For example, a person with dyslexia may struggle with inputting correctly spelled queries. Spelling skills, however, may also be influenced by fatigue, illness, or using a mobile phone while walking. All types of users can therefore at certain times experience challenges related to query input.